The Problems in Applying Authentic Assessment for Speaking Skills in Junior High School - Muhlis fajar Wicaksana; Sarwiji Suwandi; Retno Winarni; Ngadiso Ngadiso (Jurusan Tadris Bahasa Indonesia, 2019)
Various problems arise in the application of the 2013 curriculum, especially the authentic assessment system. This study tries to describe the various problems that arise, the factors that cause debate, and efforts to overcome them. This research method uses a qualitative descriptive method. Data collection techniques are carried out through observation, interviews, and document analysis. The source of information for the research came from two female teachers at Sukoharjo 1 & 3 SMPN and one male teacher from Al-Azhar Islamic Middle School 21 Solo Baru. The data validity technique is done through data triangulation. Data obtained through observation, interviews, and document analysis are all complementary. The results showed that: a) understanding the teacher about authentic assessment still varied, b) limiting the time in applying authentic assessment, c) the teacher did not check the instrument to be used, d) the teacher who often did not conduct the research process in learning, e) processing the value of learning outcomes received by the teacher is too complicated and complicated, also f) the minimum reading power of the teacher to study books about authentic assessment. One of the causes is internal and external factors. Internal factors come from within (teachers and students), while external factors come from outside the teacher's ability.Â Berbagai permasalahan muncul dalam penerapan kurikulum 2013, khususnya sistem penilaian autentik aspek keterampilan berbicara di SMP. Penelitian ini bertujuan mendeskripsikan berbagai permasalahan yang muncul, faktor-faktor yang menyebabkan permasalahan, dan upaya untuk mengatasinya. Metode penelitian ini menggunakan pendekatan deskriptif kualitatif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan analisis dokumen. Sumber informasi penelitian berasal dari dua guru perempuan di SMPN 1 & 3 Sukoharjo dan satu guru laki-laki dari SMP Islam Al-Azhar 21 Solo Baru. Teknik keabsahan data dilakukan melalui triangulasi data. Data diperoleh melalui observasi, wawancara, dan analisis dokumen semuanya saling melengkapi. Hasil penelitian menunjukkan bahwa: a) pemahaman guru tentang penilaian autentik masih bervariasi, b) keterbatasan waktu dalam penerapan penilaian autentik, c) guru tidak mau mengecek instrumen penilaian yang akan digunakan, d) guru sering tidak melakukan penilaian proses dalam pembelajaran, e) pengolahan nilai hasil belajar yang dirasakan guru terlalu rumit dan kompleks, serta f) minimnya daya baca guru untuk mengkaji buku-buku mengenai penilaian autentik. Adapun faktor penyebab permasalahan adalah faktor internal dan eksternal. Faktor internal berasal dari dalam (guru dan siswa), sedangkan faktor eksternal berasal dari luar kemampuan guru.